2022
DOI: 10.1108/cg-05-2021-0196
|View full text |Cite
|
Sign up to set email alerts
|

Audit committees’ oversight role in developing countries: evidence from Jordan

Abstract: Purpose This study aims to explore the opinions of audit committee (AC) members on the extent to which they fulfil the oversight role vested in them by the Jordanian Corporate Governance Code (JCGC). Design/methodology/approach This study uses semi-structured interviews with 18 AC members. Findings The findings suggest that although ACs largely meet the JCGC’s recommendations, their substantive oversight role in practice is limited. In particular, the responses indicate that ACs suffer from a lack of real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
(124 reference statements)
1
3
0
Order By: Relevance
“…This finding is consistent with research that has shown that meeting frequency alone does not necessarily lead to better performance (Shamsuddin and Alshahri, 2022;Rahman et al, 2019). For example, Shamsuddin and Alshahri (2022) found that in Oman, the number of annual meetings held is more than the Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022;Yasser et al, 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023;Shah et al, 2022).…”
Section: Audit Committee and Firm Performancesupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with research that has shown that meeting frequency alone does not necessarily lead to better performance (Shamsuddin and Alshahri, 2022;Rahman et al, 2019). For example, Shamsuddin and Alshahri (2022) found that in Oman, the number of annual meetings held is more than the Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022;Yasser et al, 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023;Shah et al, 2022).…”
Section: Audit Committee and Firm Performancesupporting
confidence: 82%
“…Another common view is that legal and regulatory frameworks are often weak and financial markets are less developed in developing countries, making it more difficult for investors to protect themselves from fraud and other corporate misconduct (Alhababsah, 2022; Yasser et al ., 2011). As a result, the importance of AC independence is higher in developing countries (Al-Araj, 2023; Shah et al.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that if an auditor who received high fees delivers poor audit quality, he would lose face and feel shame. This argument is also supported by Alhababsah and Nahar [27], who acknowledges the relevance of audit fees level as a measurement of audit quality in Jordan. Alhababsah and Nahar [27] reached this conclusion based on responses from 199 members of boards of directors, ACs, and auditors.…”
Section: Audit Quality and Audit Committee Expertisementioning
confidence: 72%
“…Boards of directors often exercise supervision through their operations committees, such as audit committees (Alhababsah, 2022;Pozzoli et al, 2022). Despite the fact that audit committees are supposed to be in charge of supervising risk management, there is no information about how the effectiveness of audit committees affects bank non-performing loans.…”
Section: Audit Committee and Non-performing Loansmentioning
confidence: 99%